Bibliometric Analysis of Technology Adoption for Enhancing Employee Well-being - Judijanto, Loso; Tamaela, Eduard Yohannis; Yahya, Siskawaty; Siregar, Sulaiman Efendi; Rauf, Nuzmerini (Eastasouth Institute, 2024)
This research employs bibliometric analysis to explore the intersection of technology adoption and employee well-being. By systematically retrieving and examining scholarly articles from prominent academic databases, the study highlights the evolution of technology in workplaces and its significant impact on employee wellness. Key insights are drawn from a range of bibliometric metrics, including citation analysis and co-occurrence maps, revealing trends, gaps, and emerging themes within the literature. The study demonstrates a critical shift in scholarly focus from traditional employee management practices to the integration of sophisticated technologies aimed at enhancing well-being. The results underscore the potential of technological innovations to improve workplace environments and suggest areas for further exploration, particularly in the realms of big data, e-government, and cross-disciplinary applications.